Excess Value Created as a Performance Metric and its Determination Utilizing the TEVA Measure - R. G. Ibragimov (Финансы: теория и практика, 2022)
The paper explores the excess value created (EVC) metric, which is an aggregated measure of the financial performance of a company over a multi-period measurement interval. The relevance of the study is due to the demand for practical solutions in the field of financial performance monitoring and incentive compensation, which makes it possible to achieve congruence between the interests of shareholders and the decisions of managers. The aim of the study is to build and justify a periodic financial measure that takes into account not only the current result but also the long-term consequences of management decisions. The scientific novelty of the study lies in the determination of the EVC metric via the TEVA indicator and providing the rationale for the new design of the performance measure. The result of the study is the derivation of formulas for calculating the EVC measure on multi-period and one-period intervals, which are free from restrictions on changes in the capital structure and the cost of capital, allow for a time-varying systematic risk of operating activities and possess the advantage of computational simplicity important for practical applications. The study concludes that the measurement of value created using the EVC indicator determined via TEVA makes it possible to achieve close conformity of the metric constructed to the real-world conditions with the unification of calculations in its retrospective and forecast components based on data available from historical and Pro Forma financial statements and information from the capital market.